2002
DOI: 10.1080/1357714021000066368
|View full text |Cite
|
Sign up to set email alerts
|

Periosteal Osteosarcoma: A Review of 17 Cases with Mean Follow‐upof 52 Months

Abstract: Purpose: Periosteal osteosarcomas are rare cartilage-rich bone tumours characterized by a juxtacortical eccentric position and are normally regarded oncologically as of intermediate to high grade.Their low incidence is mirrored by a small number of reported cases in the world literature. While there is general agreement that wide surgical excision is required, there is a paucity of evidence regarding adjuvant therapy. Previous reports have not indicated any consistent approach to this to allow appraisal. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 16 publications
5
44
0
3
Order By: Relevance
“…However, a review of 17 cases with a mean follow-up time of 52 months showed the encouraging effects of chemotherapy, with results indicating 100% metastasis-free survival among PO cases (3). Furthermore, the outcome indicated that it may be too prudent for the decision to use chemotherapy to be only shared with patients with high-grade PO, suggesting that chemotherapy may be routinely utilized in PO of intermediate grade (1,3,16). In the present study, chemotherapy was administered in two intermediate-grade PO patients who proved to be good responders to the treatment, and who experienced disease-free survival times of 37 and 108 months, respectively, at last follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a review of 17 cases with a mean follow-up time of 52 months showed the encouraging effects of chemotherapy, with results indicating 100% metastasis-free survival among PO cases (3). Furthermore, the outcome indicated that it may be too prudent for the decision to use chemotherapy to be only shared with patients with high-grade PO, suggesting that chemotherapy may be routinely utilized in PO of intermediate grade (1,3,16). In the present study, chemotherapy was administered in two intermediate-grade PO patients who proved to be good responders to the treatment, and who experienced disease-free survival times of 37 and 108 months, respectively, at last follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a wide excision is considered mandatory to achieve the complete removal of a tumor (1,19,20). However, a wide excision often necessitates removal of functional structures, resulting in prolonged surgery time and compromised limb function (3,8,(20)(21)(22). Furthermore, recurrences and metastases are not rare in patients undergoing a wide excision of a tumor (1,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perikraniyel veya dış kalvaryal yüzeyden gelişebilir. Diferansiye olmadığı sürece intrakraniyel uzanım izlenmez [201,202]. Kafa tabanından çok kubbede daha sık görülür [203].…”
Section: Osteosarkomunclassified